Regression analyses of the Philippine birth weight distribution - Beltrano, Elline Jade; Leong, Robert Neil F.; Co, Frumencio F. (2013)
Low birth weight has both short-term and long-term effects. It can lead to complications among infants causing neonatal deaths. Several literatures also suggested relationships between low birth weight and delayed mental and physical development. These negative effects are further magnified in developing countries, one of which is the Philippines. In this paper, birth weight is analysed through logistic, ordinary least squares, and quantile regression techniques using a sample from the 2008 National Demographic and Health Survey. Quantile regression results offer a more dynamic picture of how these correlates affect the conditional distribution of birth weight. The estimates of the marginal effects of several demographical and maternal health correlates of birth weight suggest that socially and economically impoverished mothers are more likely to have low birth weight babies. These results would recommend a focus on improving maternal health care through proper education.